Teaching and learning population and preventive health: challenges for modern medical curricula. - Régo PM; Dick M (Medical Education, 2005)
This study aimed to formally identify medical students' attitudes towards population and preventive health issues addressed in the University of Queensland's Bachelor of Medicine, Bachelor of Surgery (MBBS) programme, in response to informal student reports that population and preventive health issues were largely just matters of'common sense'.Year 2 medical students were surveyed in 1999 and 2000 using a custom-designed instrument incorporating Likert scales and requests for qualitative responses. A sample of students participated in semistructured interviews.A total of 341 students (71%) responded to the survey. Students' attitudes towards general population health issues were overwhelmingly positive, and more than 60% of students reported having a more positive attitude towards psychosocial and preventive health issues than they had when they commenced the MBBS programme. Just over half of the students, however, considered population and preventive health issues to be matters of common sense. Students reported poor role modelling by the faculty in relation to population and preventive health issues, with only 41% of students indicating they perceived a positive attitude towards psychosocial and preventive health issues in the School of Medicine. Qualitative data indicated that some students fear that the opportunity cost of dedicating study time to population and preventive health issues might endanger their future clinical knowledge, skills and management of patients.These findings have important implications for modern medical curricula. The challenge in teaching population health issues is to balance students' needs to understand and apply the principles of population and preventive health and the biopsychosocial model of patient care, with the need for them to be confident they will be able to practise safely if they do so.